1983
DOI: 10.1095/biolreprod29.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Changes in the Incubating and Brooding Turkey Hen1 1

Abstract: Turkey hens were allowed to incubate eggs and to hatch and rear young. Plasma prolactin (Prl) levels increased prior to the start of continuous incubation and rose sharply as incubation progressed to reach a peak of 1178.2 +/- 221.8 ng/ml (mean +/- SEM) just before hatching. Prl levels then fell precipitously before the hens left the nest, and returned to preincubation levels (36.8 +/- 3.4 ng/ml) by the time the poults were 2 weeks old. These results show that the high plasma concentrations of Prl found during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…These relationships are also seen in domesticated species. For instance, the onset of lay in chickens and turkeys is preceded by a rise in the circulating GH concentration which is sustained during the laying cycle (Scanes et al 1979, Williams et al 1986), declines during incubation (Harvey et al 1979, Sharp et al 1979 and increases with the brooding of young (Wentworth et al 1983). These changes reflect differences in the numbers of pituitary somatotrophs (Ramesh et al 1995(Ramesh et al , 1996 and the abundance of pituitary GH mRNA (Karatzas et al 1997).…”
Section: Seasonal Breedingmentioning
confidence: 99%
“…These relationships are also seen in domesticated species. For instance, the onset of lay in chickens and turkeys is preceded by a rise in the circulating GH concentration which is sustained during the laying cycle (Scanes et al 1979, Williams et al 1986), declines during incubation (Harvey et al 1979, Sharp et al 1979 and increases with the brooding of young (Wentworth et al 1983). These changes reflect differences in the numbers of pituitary somatotrophs (Ramesh et al 1995(Ramesh et al , 1996 and the abundance of pituitary GH mRNA (Karatzas et al 1997).…”
Section: Seasonal Breedingmentioning
confidence: 99%
“…During incubation, PRL mRNA reaches its highest level (Talbot et al, 1991;Karatzas et al, 1997) which infers that PRL is important in the maintenance of broodiness. Still it is not fully elucidated that a change in the concentration of prolactin is responsible for timing of oviposition in domestic hen (Wentworth et al, 1983) or due to longer intervals of LH surges. Also prolactic plays a role in the development of broodiness in poultry with reference to turkey and bantam hens (Sharp et al, 1988) nothing is reported in this breed.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated effect sizes (d) and P values for the comparisons of plasma PRL levels and the number of TH-ir neurons in each hypothalamic nucleus of rearing (R) and non-rearing (NR) hens at different days during the observed rearing period (n = 6/group). decline sharply (Opel and Proudman, 1989), and the hen leaves the nest and begins to display rearing behavior toward its new offspring (Wentworth et al, 1983). Indeed, species-dependent, sharp declines (bantams, Sharp et al, 1988;bar-headed geese, Dittami, 1981;common eiders, Criscuolo et al, 2002;domestic ducks, Hall, 1987; Japanese bantams, Zadworny et al, 1988;mallard ducks, Goldsmith and Williams, 1980;swans, Goldsmith, 1982; native Thai chickens, Chaiyachet et al, 2013b;and turkeys, Wentworth et al, 1983) or slow decreases (spotted sandpipers, Oring et al, 1986;Wilson's phalaropes, Oring et al, 1988;and red-necked phalaropes, Gratto-Trevor et al, 1990) in circulating PRL concentrations in hens after chick hatching have been reported (Schradin and Anzenberger, 1999).…”
Section: Introductionmentioning
confidence: 99%